The Structural Relationship among the Venture Company’s Corporate Entrepreneurship, Positive Error Management Climate, Technology Commercialization Capability, Technological Innovation Capability and Management Performance - Jang, Seung-hwan (International Review of Management and Marketing, 2026)
In high-uncertainty environments shaped by rapid technological change, venture firm performance depends not only on technological resources but also on the organizational mechanisms that transform these resources into market value. Drawing on the resource-based view, entrepreneurial orientation theory, and error management theory, this study develops and tests an integrated structural model linking technological innovation capability and technology commercialization capability to management performance through the mediating role of corporate entrepreneurship and the moderating role of positive error management climate. Survey data were collected from employees and key informants of Korean venture firms registered with a national venture association (N > 300). Structural equation modeling was employed to test the proposed hypotheses. The results reveal that both technological innovation capability and technology commercialization capability exert significant positive effects on management performance. Corporate entrepreneurship partially mediates these relationships, indicating that technological capabilities translate into superior performance when accompanied by organizational innovativeness, proactiveness, and risk-taking behaviors. Furthermore, multi-group analysis demonstrates that positive error management climate strengthens the effects of technological capabilities on performance, suggesting that learning-oriented cultures enhance the conversion of technological resources into market outcomes. This study contributes to the literature by distinguishing innovation capability from commercialization capability and integrating technological, behavioral, and cultural determinants within a single framework. The findings provide theoretical implications for extending dynamic capabilities and entrepreneurial orientation perspectives and offer practical insights for venture firms seeking sustainable competitive advantage in technology-intensive industries.